2013
DOI: 10.1038/ngeo1921
|View full text |Cite
|
Sign up to set email alerts
|

Microbial control of the dark end of the biological pump

Abstract: A fraction of the carbon captured by phytoplankton in the sunlit surface ocean sinks to depth as dead organic matter and faecal material. The microbial breakdown of this material in the subsurface ocean generates carbon dioxide. Collectively, this microbially mediated flux of carbon from the atmosphere to the ocean interior is termed the biological pump. In recent decades it has become clear that the composition of the phytoplankton community in the surface ocean largely determines the quantity and quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
302
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(313 citation statements)
references
References 69 publications
8
302
1
2
Order By: Relevance
“…Water at depths between 100 and 350 m was enriched in TDN presumably due to the lack of active autotrophs and dominance of remineralization processes of sinking particles at these depths (Shaffer, 1996;Herndl and Reinthaler, 2013). During our sampling campaign, however, no extensive phytoplankton blooms were detected.…”
Section: Resultsmentioning
confidence: 83%
“…Water at depths between 100 and 350 m was enriched in TDN presumably due to the lack of active autotrophs and dominance of remineralization processes of sinking particles at these depths (Shaffer, 1996;Herndl and Reinthaler, 2013). During our sampling campaign, however, no extensive phytoplankton blooms were detected.…”
Section: Resultsmentioning
confidence: 83%
“…Particle flux, which varies seasonally in magnitude and composition (Collins et al, 2011), likely contributes to the observed seasonality at 890 m, which is at the bottom of the water column. Particles are believed to be the source of key substrates for bacteria in the deep ocean and likely transport organic nutrients from the surface to the bottom, where they may become entrained in the nepheloid layer or land on the sea floor, degrade and affect nearby overlying waters (Francois et al, 2002;Herndl and Reinthaler, 2013). Therefore, the longer residence time of particles and their associated organic matter at or near the sea floor, compared with mid-water, likely leads to stronger seasonality there.…”
Section: Discussionmentioning
confidence: 99%
“…However, relatively little is known about whether these characteristics are consistent with or influence subsurface microbial communities, especially those below the euphotic zone. The mesopelagic region is of great biogeochemical interest, as it is the site of much of the Earth's carbon remineralization (Aristegui et al, 2009;Herndl and Reinthaler, 2013), as well as the nitrogen (Zehr and Ward, 2002) and sulfur cycles (Canfield et al, 2010), particularly in oxygen minimum zones that are found in association with coastal upwelling (Wright et al, 2012). The San Pedro Ocean Time Series (SPOT) provides an opportunity to study the entire water column, from surface to mesopelagic, in a coastal seasonal upwelling system that includes an oxygen minimum at the bottom of the water column.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has recently been revealed that the deep-sea biogeochemical cycles are more complex than previously expected and that the mismatch between the organic carbon supply and microbial heterotrophic demand has led to imbalances in some oceans (1-4). Currently, the contribution of chemolithoautotrophy and mixotrophy to the biogeochemical cycle (e.g., dark carbon fixation coupled with nitrification and sulfur oxidations) is also recognized as another significant organic carbon source in the dark ocean (3,5,6). It has been estimated that the dissolved inorganic carbon fixation in the dark ocean by these organisms could be on the same order-of-magnitude as heterotrophic biomass production (3,5).…”
mentioning
confidence: 99%